Visualization of clonal expansion after massive depletion of cells carrying the bovine leukemia virus (BLV) integration sites during the course of disease progression in a BLV naturally-infected cow: a case report - Susumu Saito; Kazuyoshi Hosomichi; Meripet Polat Yamanaka; Tetsuya Mizutani; Shin-nosuke Takeshima; Yoko Aida (Retrovirology, 2022)
Abstract Bovine leukemia virus (BLV) infects cattle, integrates into host DNA as a provirus, and induces malignant B-cell lymphoma. Previous studies have addressed the impact of proviral integration of BLV on BLV-induced leukemogenesis. However, no studies have monitored sequential changes in integration sites in which naturally infected BLV individuals progress from the premalignant stage to the terminal disease. Here, we collected blood samples from a single, naturally infected Holstein cow at three disease progression stages (Stage I: polyclonal stage, Stage II: polyclonal toward oligoclonal stage, Stage III: oligoclonal stage) and successfully visualized the kinetics of clonal expansion of cells carrying BLV integration sites using our BLV proviral DNA-capture sequencing method. Although 24 integration sites were detected in Stages I and II, 92% of these sites experienced massive depletion in Stage III. Of these sites, 46%, 37%, and 17% were located within introns of Refseq genes, intergenic regions, and repetitive sequences, respectively. At Stage III cattle with lymphoma, only two integration sites were generated de novo in the intergenic region of Chr1, and the intron of the CHEK2 gene on Chr17 was significantly increased. Our results are the first to demonstrate clonal expansion after the massive depletion of cells carrying BLV integration sites in a naturally infected cow.